2017
DOI: 10.21149/8140
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen-insect interaction candidate molecules for transmission-blocking control strategies of vector borne diseases

Abstract: Zumaya ResumenObjetivo. Analizar el conocimiento actual de las interacciones patógeno-insecto susceptibles a incluirse en el diseño de estrategias moleculares para el control de enfermedades transmitidas por vectores. Material y métodos. Se examinaron los agentes causales de la malaria, el dengue y la enfermedad de Chagas, y las moléculas de insectos que participan en interacciones durante la infección de sus vectores. Resultados. Se presentan moléculas de patógenos que participan en la invasión del intestino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Hence, the triatomines with the presence of the parasite Trypanosoma cruzi have a clear footprint that makes them distinguishable from others. Studies conducted with different species of triatomines have shown that the parasite generates metabolic changes in the insect (IEEE Staff 2010; Zumaya-Estrada et al 2018; Erny and Masuda 2022), due to interactions between the insect intestine and the parasite in its different life stages.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the triatomines with the presence of the parasite Trypanosoma cruzi have a clear footprint that makes them distinguishable from others. Studies conducted with different species of triatomines have shown that the parasite generates metabolic changes in the insect (IEEE Staff 2010; Zumaya-Estrada et al 2018; Erny and Masuda 2022), due to interactions between the insect intestine and the parasite in its different life stages.…”
Section: Discussionmentioning
confidence: 99%
“…Some successful examples against transmission of Plasmodium berghei by Anopheles stephensi (108), P. vivax (109) by A. dirus (110), P. falsiparum by A. gambiae (111), and Leishmania infantum by Lutzomyia longipalpis (112) have been reported in the literature, showing this strategy as promising and possibly helpful in interrupting distinct pathogen transmission cycle. Notwithstanding the potential of TBVs, they do not directly protect humans, so there is resistance to their use in public health programs (113). In 1980, there were about 95 species of arboviruses cataloged in Brazil alone, but this number has doubled in the last three decades and today 210 arboviruses circulate in the country.…”
Section: Immunoprophylactic and Biological Control Approachesmentioning
confidence: 99%